2018
DOI: 10.7759/cureus.2957
|View full text |Cite
|
Sign up to set email alerts
|

A Strange Case of Dissociative Identity Disorder: Are There Any Triggers?

Abstract: We discuss a strange case of dissociative identity disorder, also known as multiple personality disorder. This article describes the case of a 55-year-old Caucasian woman with a history of substance use disorder with seven personalities. The patient describes a couple of triggers for her condition. More research is needed to understand these triggers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The existence of multiple and separate identity states repeated memory lapses, and severe distress or misfunctioning in day-to-day functioning are some examples of these criteria. Dissociative identity disorder also referred to as multiple personality disorder, is a condition in which the personality of a person is split into two or more separate personalities (Rehan et al,2018).…”
Section: Dissociative Identity Disorder (Did)mentioning
confidence: 99%
“…The existence of multiple and separate identity states repeated memory lapses, and severe distress or misfunctioning in day-to-day functioning are some examples of these criteria. Dissociative identity disorder also referred to as multiple personality disorder, is a condition in which the personality of a person is split into two or more separate personalities (Rehan et al,2018).…”
Section: Dissociative Identity Disorder (Did)mentioning
confidence: 99%
“…Ego states usually manifest unconsciously when a subject is faced with adverse environmental and social triggers. 7 Alters are interpreted as separate states of being, that have been reported to express an individual's set of ideas, values, memories, personality, CT and MRI scans. Reinders et al conducted a study using whole brain correlation analysis in a subset of patients with DID observed significant reduction in the cortical volume in areas such as the insula, anterior cingulate and parietal regions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In some instances, an aura has been reported to supersede an alter being pulled from the unconscious to the subconscious. 7 The memories that many of the alters elicit are often entirely different from what the original persona has experienced, so much so that it cannot yet be explained by dementia or any other medical condition. 8 DID and other psychiatric disorders such as schizophrenia have some diagnostic features in common that can often make it challenging to differentiate these comparable conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple reports published on the correlation between alcohol abuse and ADHD [4]. Alcohol misuse was found to be more frequent in people who were diagnosed with ADHD at the childhood stage [6] and the misuse can also lead to some personality changes [7]. Brinkman et al showed that the starting age for alcohol consumption is lower for adolescents suffering from ADHD as opposed to healthy individuals [8].…”
Section: Introductionmentioning
confidence: 99%